Immunotoxin Methods and Protocols - Hall, Walter A.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2001)
More potent and selective for killing cancer cells than chemotherapy, immunotoxins constitute a new class of human therapeutics that have widespread applications and a potential that has not yet been fully recognized. In Immunotoxin Methods and Protocols, leading experts from laboratories around the world describe in step-by-step detail their cutting-edge methods for developing and applying these powerful proteins. The conjugates created by these researchers contain entire monoclonal antibodies, single chain antibody fragments, and cytokines as their carrier ligands. Their toxic portion can include such conventional chemotherapeutics as doxirubicin, such ribosome-inactivating proteins as the ricin A chain or saporin, or such bacterial toxins as diptheria toxin. Also described are a variety of applications that demonstrate the versatility of these agents, including the treatment of primary malignant brain tumors, the generation of selective brain lesions to localize critical functions, and the targeting of the AIDS virus. Each readily reproducible method is optimized for experimental success with hands-on instructions, invaluable notes on pitfalls to avoid, and informative explanations of why certain steps are necessary. Authoritative and highly practical, Immunotoxin Methods and Protocols provides today's cancer researchers, neuroscientists, and oncologists with state-of-the-art tools for exploring these powerful biological agents and their rapidly increasing applications.
Immunotoxin Construction and Development -- Development and Activities of the BR96-Doxorubicin Immunoconjugate -- CD7-Specific Single Chain Fv Immunotoxins -- Recombinant Fusion Toxins Directed Against the Human Granulocyte-Macrophage Colony Stimulating Factor (GM-CSF) Receptor -- Synthesis of Monensin Derivatives and Their Effect on the Activity of Ricin A-Chain Immunotoxins -- Purification and Conjugation of Type 1 Ribosome-Inactivating Proteins -- Comparison of Immunotoxins Bearing a Single Saporin Molecule with Multiple Toxin Conjugates -- Modulation of Growth Factor Receptor Expression by Irradiation for Immunotoxin Targeting -- Quantification of Immunotoxin Number for Complete Therapeutic Response -- In Vitro Studies of Ricin A-Chain-Induced Vascular Leak Syndrome -- Oncologic Applications of Immunotoxins -- Immunotoxin Treatment of Brain Tumors -- Cytotoxins Directed at Interleukin-4 Receptors as Therapy for Human Brain Tumors -- Bispecific Monoclonal Antibodies for the Targeting of Type I Ribosome-Inactivating Proteins Against Hematological Malignancies -- Tyrosine Kinase Inhibitors Against EGF Receptor-Positive Malignancies -- Targeting Tumor Vasculature Using VEGF-Toxin Conjugates -- Gene Therapy With Immunotoxins -- Alternative Applications of Immunotoxins -- Effects of Selective Immunotoxic Lesions on Learning and Memory -- Targeting Toxins to Neural Antigens and Receptors -- In Vivo Testing of Anti-HIV Immunotoxins.
Keywords: Immunology; Immunology